2000
DOI: 10.1162/089892900562147
|View full text |Cite
|
Sign up to set email alerts
|

Language Processing Modulated by Literacy: A Network Analysis of Verbal Repetition in Literate and Illiterate Subjects

Abstract: Abstract& Previous behavioral and functional neuroimaging data indicate that certain aspects of phonological processing may not be acquired spontaneously, but are modulated by learning an alphabetic written language, that is, learning to read and write. It appears that learning an alphabetic written language modifies the auditory-verbal (spoken) language processing competence in a nontrivial way. We have previously suggested, based on behavioral and functional neuroimaging data, that auditory-verbal and writte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
114
1
5

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 158 publications
(130 citation statements)
references
References 93 publications
10
114
1
5
Order By: Relevance
“…But note that Reis and Castro-Caldas (1997) found that illiterates also performed much worse than literates on pseudoword repetition (replicated in Castro-Caldas, Petersson, Reis, Stone-Elander, & Ingvar, 1998). Petersson and colleagues have argued that this is related to an inability to handle certain aspects of sub-lexical-phonological structure (Petersson, Reis, Askelöf, Castro-Caldas, & Ingvar, 2000) and suggest that phonological representations, or the processing of these representations, are differently developed in literates and illiterates (Petersson et al, 2000cf. Smith et al, 2014).…”
Section: Pseudoword Repetitionmentioning
confidence: 99%
“…But note that Reis and Castro-Caldas (1997) found that illiterates also performed much worse than literates on pseudoword repetition (replicated in Castro-Caldas, Petersson, Reis, Stone-Elander, & Ingvar, 1998). Petersson and colleagues have argued that this is related to an inability to handle certain aspects of sub-lexical-phonological structure (Petersson, Reis, Askelöf, Castro-Caldas, & Ingvar, 2000) and suggest that phonological representations, or the processing of these representations, are differently developed in literates and illiterates (Petersson et al, 2000cf. Smith et al, 2014).…”
Section: Pseudoword Repetitionmentioning
confidence: 99%
“…In fact, conventional interventions often produce more permanent neurological changes than do drugs. Learning to read alters the way language is processed in the brain (Petersson 2000). Enriched rearing environments have been found to increase dendritic arborisation and to produce synaptic changes, neurogenesis, and improved cognition in animals (Walsh et al 1969;Greenoug and Volkmar 1973;Diamond et al 1975;Nilsson et al 1999).…”
Section: Education Enriched Environments and General Healthmentioning
confidence: 99%
“…The dominant cooperative framework (Buchanan et al 2001) of Western society has developed in such a way that an illiterate person is excluded from many opportunities and unable to participate in many aspects of modern life. Despite these enormous and partially coercive pressures, and despite the fact that literacy profoundly changes the way the brain processes language (Petersson 2000), literacy is not deemed to be problematic. The costs of illiteracy are placed on the individual who deliberately avoids education.…”
Section: Cheating Positional Goods and Externalitiesmentioning
confidence: 99%
“…Both the insula Paulesu et al, 1993) and the basal ganglia Monchi, Petrides, Petre, Worsley, & Dagher, 2001) have also been observed in tasks involving working memory. In particular, it has been suggested that the insular cortex is an integral part of the phonological loop (Paulesu et al, 1993;Petersson, Reis, Askelof, Castro-Caldas, & Ingvar, 2000). However, the more specific functional roles of these activations as related to working memory remain unclear (for reviews, see Cabeza & Nyberg, 2000;Fletcher & Henson, 2001).…”
Section: Verbal Working Memorymentioning
confidence: 99%
“…3). The superior temporal cortex, in addition to the inferior frontal (BA 44/45), supramarginal (BA 40) and the insular cortices, has been proposed to constitute the phonological loop in working memory (Paulesu et al, 1993;Petersson et al, 2000). Whether the superior temporal cortex is an integral part of the core verbal working memory network can be discussed.…”
Section: The Irrelevant Speech Effectmentioning
confidence: 99%